Debt-For-Equity Swaps under a Rational Expectations Equilibrium - Errunza, Vihang R.; Moreau, Arthur F. (Journal of Finance, 1989)
This paper analyzes LDC debt-for-equity swaps under a rational expectations equilibrium. Under full information, the swap can never be strictly preferred by the LDC, the MNC, and the bank. Under the postulated informational asymmetry assumptions the same results obtain, leading to the “lemons” market in reverse. Under rational expectations, the swap can only occur if the loan is correctly valued relative to all private information in the economy. Given that some swaps do occur, future models must reflect the unique features of swaps.